Improve password Authentication by using QR code & OTP. - Ibrahim, Amjed Abdalla Haroon; Ali, Ibrahim Moham Ahmed ed; Eltayeb, Yahia Hayder Elheber (Arab Journal for Humanities & Social Sciences, 2025)
an Authentication is the process of determining whether a user should be allowed access to a particular system or resources it is a critical area of security research and practice, they are many techniques used in password authentication such as text password, graphical password and in this paper we used QR code and OTP to improve password authentication, also we used PHP, HTML, and CSS in design web system, AES algorithm to encrypted text and composer program to send the encrypted text to user email. As result the dates in the web are binge more secure.